Implementasi Sistem Akuntabilitas Kinerja Instansi Pemerintah qPada Badan Kepegawaian Negara Di Kota Manado - Pangerapan, Jenni; Posumah, Johnny Hanny; Rompas, Welson (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: Government Regulation No. 8/2006 mentioned that the GovernmentPerformance Accountability System is at least able to inform the development ofthe output of each activity and the results of each program as established in theimplementation of the budget document. Under Law 1/2004, the implementationof the budget document, compiled by the minister / head of the institution, outlinedthe objectives to be achieved, functions, programs and details of activities, thebudget provided for achieving these goals, and plan withdrawals each unit ofwork, and revenue estimated at Kanreg XI BKN Manado. This study usedqualitative methods. Source of data / research respondents are not quantified, asneeded research. Data collection techniques using interview guide. The dataanalysis technique used is descriptive qualitative. The results showed: (1) Datareduction was found that policy Government Performance Accountability Systemhas good staying note again the things that have not been completed (2)Presentation of data found there are still things that need to be considered is theHuman Resources (Employee) , Infrastructures, and time Services. Based on theresults of the statistical analysis conclude that the implementation of GovernmentPerformance Accountability System and positive effect on the Internal EmployeesKanreg XI BKN External Employees in Manado and Other Agencies. Based onthe conclusion of the study suggested: (1) Judging from all the important aspectsof this program, the government should pay more attention again WorkingFacilities and should improve the quality of service for employees who take careof personnel administration can get good service and deserve from this policy (2)Seen of Human Resources (employee) that is, more attention again due to the factthat there is in the field is still not quite in accordance with the existing workloadso that all parties, not just employees in Kanreg XI BKN but employees of otheragencies also may pleased with this Policy.Keywords: Performance Accountability System, Government Agencies